Gain-of-Function Variants in Dilated Cardiomyopathy. - Cowan, Jason R; Salyer, Lorien; Wright, Nathan T; Kinnamon, Daniel D; Amaya, Pedro; Jordan, Elizabeth; Bamshad, Michael J; Nickerson, Deborah A; Hershberger, Ray E (Circ Genom Precis Med, 2020)
BACKGROUND: Dilated cardiomyopathy (DCM) is a genetically heterogeneous cardiac disease characterized by progressive ventricular enlargement and reduced systolic function. Here, we report genetic and functional analyses implicating the rat sarcoma signaling protein, SOS1 (Son of sevenless homolog 1), in DCM pathogenesis. METHODS: Exome sequencing was performed on 412 probands and family members from our DCM cohort, identifying several variants with potential disease involvement. As several lines of evidence have implicated dysregulated rat sarcoma signaling in the pathogenesis of DCM, we assessed functional impact of each variant on the activation of ERK (extracellular signal-regulated kinase), AKT (protein kinase B), and JNK (c-Jun N-terminal kinase) pathways. Relative expression levels were determined by Western blot in HEK293T cells transfected with variant or wild-type human expression constructs. RESULTS: A rare variant [c.571G>A, p.(Glu191Lys)] was found to segregate alongside an A-band truncating variant in a pedigree with aggressive, early-onset DCM. Reduced disease severity in the absence of the variant suggested its potential involvement as a genetic risk factor for DCM in this family. Exome sequencing identified 5 additional variants with potential disease involvement in 4 other families [c.1820T>C, p.(Ile607Thr); c.2156G>C, p.(Gly719Ala); c.2230A>G, p.(Arg744Gly); c.2728G>C, p.(Asp910His); c.3601C>T, p.(Arg1201Trp)]. Impacted amino acids occupied a number of functional domains relevant to SOS1 activity, including the N-terminal histone fold, as well as the C-terminal REM (rat sarcoma exchange motif), CDC25 (cell division cycle 25), and PR (proline-rich) tail domains. Increased phosphorylated ERK expression relative to wild-type levels was seen for all 6 variants, paralleling known disease-relevant signaling profiles. CONCLUSIONS: These data support gain-of-function variation in as a contributing factor to isolated DCM.

Multigenic Disease and Bilineal Inheritance in Dilated Cardiomyopathy Is Illustrated in Nonsegregating LMNA Pedigrees. - Cowan, Jason R; Kinnamon, Daniel D; Morales, Ana; Salyer, Lorien; Nickerson, Deborah A; Hershberger, Ray E (Circ Genom Precis Med, 2018)
BACKGROUND: We have previously described 19 pedigrees with apparent lamin ()-related dilated cardiomyopathy (DCM) manifesting in affected family members across multiple generations. In 6 of 19 families, at least 1 individual with idiopathic DCM did not carry the family's variant. We hypothesized that additional genetic cause may underlie DCM in these families. METHODS: Affected family members underwent exome sequencing to identify additional genetic cause of DCM in the 6 families with nonsegregating variants. RESULTS: In 5 of 6 pedigrees, we identified at least 1 additional rare variant in a known DCM gene that could plausibly contribute to disease in the variant-negative individuals. Bilineal inheritance was clear or presumed to be present in 3 of 5 families and was possible in the remaining 2. At least 1 individual with a variant also carried a variant in an additional identified DCM gene in each family. Using a multivariate linear mixed model for quantitative traits, we demonstrated that the presence of these additional variants was associated with a more severe phenotype after adjusting for sex, age, and the presence/absence of the family's nonsegregating variant. CONCLUSIONS: Our data support DCM as a genetically heterogeneous disease with, at times, multigene causation. Although the frequency of DCM resulting from multigenic cause is uncertain, our data suggest it may be higher than previously anticipated.